Decentralization of climate governance in Pakistan: Exploring a polycentric approach - Humaira Atiq; Muhammad Irfan Mahsud; Muhammad Iqbal Uddin Arif (Faculty of Social and Political Science, Universitas Airlangga, 2026)
Climate change is a transnational problem, that requires localized collective actions. Compared to China and the US which contributes 27% and 11% to global carbon emissions, respectively, Pakistan contributes less than 1% but is among the top ten most vulnerable countries to climate catastrophes. These threats are further escalated by the country’s highly centralized governance structure. These study focuses on the decentralization of climate policies in Pakistan, followed by a polycentric governance system, and highlights its importance in responding to the dynamic nature of climate change in the country. Grounded in Polycentric Governance Theory, a qualitative, deductive research design way employed, relying on primary and secondary data sources. The study reveals that after the 18th amendment in Pakistan, the responsibility related to climate policies has increased on the subnational government; however, its effect remains limited due to constant economic constraints, weak coordination among different governmental bodies, and dependency on international climate finance. This demonstrates that polycentric governance offers a commendable framework for making strong climate responses by involving local actors and providing region-specific solutions. This study concluded policymakers might prioritize intergovernmental coordination, expand subnational budget capacity and use carbon sinking mechanisms as a major tool for reducing climate change impacts.